Innovations systems and learning processes in the EU and US regions - Malgorzata Runiewicz-Wardyn (University of California, Institute of Urban and Regional Development (IURD), 2009)
European regions suffer from weaker regional clusters and cluster portfolios than their peers in the United States (U.S.) or elsewhere in the world. The latter can be an important factor keeping them behind in global competition. The following research paper focuses both on regions as systems of innovation and as technology clusters. The selected case studies examine the development as well as structure and types of collaboration networks in the two leading Information and Communications Technologies (ICT) clusters in the U.S. and EU: Silicon Valley in California and Kista cluster of Stockholm Region in Sweden.
Keywords: 330